THE EFFECT OF STUDY HABITS ON TUTEP SCORE IMPROVEMENT - Fergina, Ana; Prancisca, Stella; Barella, Yusawinur; Ghazy, Ahmad; Rizqi, Muhammad Ainur (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Study habit is key to the success of the learning process. The study habit can be obtained when students have the intention to do so. Generally, the intention arises from repeated actions. In the TUTEP training class, the habits of the students during the training program can determine the test result. Thus, this study aims to examine the effect of study habits among the students or trainees on increasing their TUTEP scores. A descriptive-correlation method was used to describe the positive day-to-day habits that the trainees did to increase their TUTEP scores. The study involved respondents who attended the TUTEP training class and obtained a significant improvement in their TUTEP score before and after participating in the training. The main instrument in this study was the Palsane and Sharma Study Habit Inventory (Looyeh et al., 2017). The instrument has eight sub-scales of study habits. The results indicated that the significant test obtained was a ttest value of 0.738, where the ttest value was greater than ttable (0.738 0.254). In other words, it can be concluded that there is a significant relationship between study habits and increased TUTEP scores of the trainees. Furthermore, based on the highest average value (mean) of study habits which was obtained from respondents, three indicators yielded the highest scores, namely the exam (4.66), the health (4.59), and the time management indicators (4.36).